Mesenchymal Stem Cells Derived from Dental Pulp: A Review - Edgar Ledesma-Martínez; Víctor Manuel Mendoza-Núñez; Edelmiro Santiago-Osorio (Stem Cells International)
The mesenchymal stem cells of dental pulp (DPSCs) were isolated and characterized for the first time more than a decade ago as highly clonogenic cells that were able to generate densely calcified colonies. Now, DPSCs are considered to have potential as stem cell source for orthopedic and oral maxillofacial reconstruction, and it has been suggested that they may have applications beyond the scope of the stomatognathic system. To date, most studies have shown that, regardless of their origin in third molars, incisors, or exfoliated deciduous teeth, DPSCs can generate mineralized tissue, an extracellular matrix and structures type dentin, periodontal ligament, and dental pulp, as well as other structures. Different groups worldwide have designed and evaluated new efficient protocols for the isolation, expansion, and maintenance of clinically safe human DPSCs in sufficient numbers for various therapeutics protocols and have discussed the most appropriate route of administration, the possible contraindications to their clinical use, and the parameters to be considered for monitoring their clinical efficacy and proper biological source. At present, DPSC-based therapy is promising but because most of the available evidence was obtained using nonhuman xenotransplants, it is not a mature technology.